O trabalho policial e a lei: um estudo de caso da Polícia Militar em Belo Horizonte - Mateus Renno Santos (2012)
It is common saying that the police officers are law enforcers. This would be their function, and fundamental part of their work. The research treats this affirmative as a hypothesis, and proposes to test it, opposing the legislation that deals with the police function with their everyday practice, measured from the incident reports maintained by the agents. Function and police practice are treated as different concepts, that could be compared with each other, resulting in a description of the police based on its goals, from characteristics currently expressed on the legislation, and in what police officers actually do in their daily work. Beyond the highlighting of several characteristics of the police, the research also showed significant deficiencies on the law describing the corporation. It applies broad concepts that do not specify for what the police serve. Fact is, however, that while not described in law, police officers perform certain activities in their work. It would be necessary then to identify, if not form law, from where the police work derive. It was demonstrated that the police work is much more dependent on the demands addressed to the police from various spheres of society, than on so many documents that would serve to formalize certain demands, which are considered relevant and legitimate. About the police work, it was shown that a good part of the activities recorded by agents have little association with the concept of public safety, present in abundance in the legislation, and fewer still requires that lethal force is applied. Most of the demands met by police officers have no direct correspondence to the criminal aspect of police work, despite so many instruments, guidelines and qualifications aimed almost exclusively in this function of the police.